Evaluating Disability-Related Quality of Life in Women With Chronic Pelvic Pain. Issue 8 (August 2020) - Ye, Alice L.; Adams, William; Westbay, Lauren C.; Fitzgerald, Colleen M.
Abstract : Objectives: The primary aim of this study was to describe quality of life (QOL) in women with chronic pelvic pain using the Pain Disability Index (PDI). A secondary goal was to assess the measurement properties and validity of the PDI for this population. Methods: This study was a cross-sectional retrospective chart review. In the setting of an outpatient female pelvic pain clinic, we included data from an initial evaluation of patients 16 years and older with chronic pelvic pain (N = 317) from 2012 to 2017. Quality of life was measured using the PDI and previously validated measures for depression and anxiety. Results: The mean PDI score across all patients was similar to previously reported means for similar chronic pain populations. Patients experienced the most disability in their sexual activities. The most common cause of chronic pelvic pain was pelvic floor myofascial pain. Common diagnostic categories covered gynecologic, urologic, gastrointestinal, musculoskeletal, and neurological causes. The PDI was unable to discriminate between diagnoses. On average, patients qualified for mild depression and anxiety diagnoses. Results from a confirmatory factor analysis revealed the original factor structure for the PDI fits this population. Conclusions: The PDI shows promise as a questionnaire for QOL and could be a valuable clinician tool for tracking QOL in the chronic pelvic pain population. Additional research should be focused on assessing its ability to measure minimum clinically significant change over time.